Cosmological Analysis of Modified Holographic Ricci Dark Energy in Chern-Simons Modified Gravity - Sarfraz Ali; M. Jamil Amir (Advances in High Energy Physics)
In this paper, we study the cosmological analysis of the modified holographic Ricci dark energy model and reconstruct different scalar field models in the context of Chern-Simons modified gravity. We investigate the deceleration parameter, which shows that the universe is in the accelerating expansion phase. The equation of state parameter in this case also favors the fact that dark energy is the dominant component of universe, which is responsible for the accelerated expansion. A number of scalar fields, such as quintessence, tachyon, K-essence, and dilaton models, are reconstructed using modified holographic Ricci dark energy model in the context of dynamical CS modified gravity. The quintessence and K-essence models represent exponentially increasing behaviors, while tachyon model shows decreasing behavior. Unfortunately, the dilaton model has no numerical solution for modified holographic Ricci dark energy model in the framework of dynamical Chern-Simons modified gravity.